2020
DOI: 10.1099/ijsem.0.004505
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrobacter psychrotolerans sp. nov., a cold-adapted bacterium isolated from Antarctic soil

Abstract: A novel cold-tolerant bacterium, designated strain YJ56T, was isolated from Antarctic soil collected from the Cape Burk area. Phylogenetic analysis through 16S rRNA gene sequence similarity revealed that strain YJ56T was most closely related to the genus Pseudarthrobacter , including Pseudarthrobacter oxydans DSM 20119T (99.06 % similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…In our previous study, amplicon deep sequencing of the 16S rDNA V3-V4 region revealed that an unclassi ed species of the genus Pseudarthrobacter with approximately 14% relative abundance was potentially psychrotolerant and noticeably enriched in the rhizosphere soil at the maturing stage of the perennial sweet sorghum N778 aerial and primary root (Lu et al, 2022). In this study, OTU1262 was shown to be particularly abundant in the root sample of perennial sweet sorghum N778 during the maturing stage and to be closely related to the well-known cold-adapted bacterium Pseudarthrobacter psychrotolerans YJ56, which was isolated from Antarctic soil (Shin et al, 2020). Based on the combined ML phylogenetic tree of OTU1262 (16S rDNA V5-V7 region) and OTU2574 (16S rDNA V3-V4 region) (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…In our previous study, amplicon deep sequencing of the 16S rDNA V3-V4 region revealed that an unclassi ed species of the genus Pseudarthrobacter with approximately 14% relative abundance was potentially psychrotolerant and noticeably enriched in the rhizosphere soil at the maturing stage of the perennial sweet sorghum N778 aerial and primary root (Lu et al, 2022). In this study, OTU1262 was shown to be particularly abundant in the root sample of perennial sweet sorghum N778 during the maturing stage and to be closely related to the well-known cold-adapted bacterium Pseudarthrobacter psychrotolerans YJ56, which was isolated from Antarctic soil (Shin et al, 2020). Based on the combined ML phylogenetic tree of OTU1262 (16S rDNA V5-V7 region) and OTU2574 (16S rDNA V3-V4 region) (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…The lipid analysis appeared to capture the characteristic cellular fatty acid content of closely related strains of each species. 11) 12) 13) 14) 15) 16) 17) However, it was not entirely clear due to the lack of standards. Related species of SO_005 ( Papiliotrema laurentii ) was known to produce lipids from D-Xyl, and studies on productivity and lipid composition were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic trees generated with the maximum-likelihood and maximum-parsimony methods can be seen in Figs S1 and S2 (available in the online version of this article). Based on 16S rRNA gene similarity and the phylogenetic trees, P. sulfonivorans ALL T [25,26], P. siccitolerans 4J27 T [27], P. phenanthrenivorans Sphe3 T [5] and P. psychrotolerans YJ56 T [28] were selected as the reference strains for further analyses under the same conditions.…”
Section: S Rrna Gene Sequence Phylogenymentioning
confidence: 99%
“…phenanthrenivorans Sphe3 T [5] and P. psychrotolerans YJ56 T [28] were selected as the reference strains for further analyses under the same conditions.…”
Section: S Rrna Gene Sequence Phylogenymentioning
confidence: 99%